PROTECTION OF LEGAL RIGHTS OF BORROWERS WHO ARE HARMED DUE TO ILLEGAL INFORMATION TECHNOLOGY-BASED LOANS - Restu Adi Putra (Jurnal Scientia, 2023)
Technology-based loans, known as online loans, are increasingly in demand by the public. The easy and fast process of disbursing loan funds is one of the reasons people are interested in using online loan services. The party authorized to oversee the implementation of online loans is the Financial Services Authority (OJK). The presence of online loans still leaves legal problems, namely there are still many service providers who are not licensed or who are known to be illegal. This makes legal protection for debtors as loan recipients very important to provide in order to protect against losses due to illegal online loans. To answer these problems, the type of research used is normative juridical by examining various laws and literature that are relevant to the theme discussed. So this study came to the conclusion that online loans made by illegal service providers do not fulfill the subjective element in the terms of a valid agreement, so the agreement can be canceled.